DESIGN SCENARIO AND ANALYSIS FOR PRELIMINARY SPECIFICATION OF STEAM GENERATOR IN THE PELUIT-40 - Byan Wahyu Riyandwita; Muhammad Subhan; Topan Setiadipura; Almira Citra Amelia; Sri Hastuty; Purwo Kadarno; Farisy Yogatama Sulistyo (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2023)
The helical steam generator is connected to an HTGR-type nuclear reactor called PeLUIt-40 for steam production. Steam is used to generate electricity and hydrogen. A once-through helical tube bundle was employed because of its ability to endure mechanical stress due to thermal expansion, high resistance to flow-induced vibrations, and better thermal performance compared to a straight tube one. To produce the targeted steam, a design analysis of the once-through helical steam generator needs to be conducted. A quick evaluation method was used to predict the preliminary specifications required for steam production. Simple thermodynamic calculations combined with empirical heat transfer coefficients covering convective and boiling processes at constant pressure were used to carry out the analysis. Two scenarios were conducted to evaluate the design choice based on the previous design of RDE-10.